Estrarre il soggetto - Curti, Pier Giorgio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The paper aims to investigate the issue of the genesis and emergence of the subject in the peculiar debate between Lacan and Hyppolite upon the Freudian writing Negation (Verneinung). Along with a brief description of a clinical case, characterized by the patient’s dream of the psychoanalyst as a dentist extracting his patient’s teeth (a metaphor for his subjectivity/symptomatology), the author highlights the emergence of subject through the fundamental notion of original repression (Ur-Verdrängung), structural model for all the future repressions and for the articulation of the subject. Furthermore, the symbol of negation owns an important role in the emergence of subjectivation, led by two functions: the judgement of attribution and the judgement of existence. Both for Hyppolite and Lacan, in fact, these two psychical functions are constitutive in the origin of the thought because they permit, respectively, the subject to accede the difference between introjection and expulsion, good and bad, (this way defining the inside-outside of the subject and, eventually, reality principle) and the difference between existing and non-existing.